PCR amplification and cloning of six target genes from Burkholderia pseudomallei - Arifah, Adini Qisthi; Mohamad Nadhan, Hani Nuramalina; Ismail, Shuhaib Ar Rumy; Raih, Mohd Firdaus; Muhamad Bunnori, Noraslinda; Mohamed Rehan, Aisyah (2016)
Burkholderia pseudomallei (B. pseudomallei) is an aerobic Gram negative bacteria and a causative agent of melioidosis, a disease endemic in several regions worldwide including Southeast Asia and Northern Australia. Melioidosis can be fatal in human, where it causes fever and is commonly present with pneumonia, with or without septicaemia. Treating melioidosis is a challenge, due to its intrinsic resistance to many antibiotics, and occurrence of latent infection. This study is part of a larger project to purify and characterise target proteins from B. pseudomallei to gain fundamental knowledge on how this bacterium behaves, and thus providing us strategies to combat them. In this report, six target genes predicted to be essential by Transposon-Directed Insertion site Sequencing (TraDIS) technique were selected for PCR amplification and cloning trials. Out of the six target genes, three genes encode for hypothetical proteins (BPSL0084, BPSL0086, and BPSL1060), two genes encode for putative annotated protein (BPSL0398 and BPSL1192) and one gene (BPSL1549) encodes for B. pseudomallei lethal factor 1. Genomic DNA of B. pseudomallei strain D286 and K96243 is obtained from School of Biosciences & Biotechnology, UKM. All six target genes were successfully amplified. Sufficient concentration of purified attBPCR products for all target genes was obtained after nested PCR. This is then utilized in the BP recombination reactions to create the entry clones. The entry clones were transformed into Escherichia coli (E. coli) DH5α™ competent cells and plated onto LB agar plate supplemented with 50 µg/mL kanamycin. The positive clones were screened using colony PCR and BsrGI restriction enzyme digestion. At the time of writing, three target genes were successfully cloned and validated by sequencing. In future projects, the entry clones can then be easily transferred into various expression vectors to be expressed and purified for diverse functional protein studies.